2011
DOI: 10.1002/bit.24403
|View full text |Cite
|
Sign up to set email alerts
|

The chemical formula of a magnetotactic bacterium

Abstract: Elucidation of the chemical logic of life is one of the grand challenges in biology, and essential to the progress of the upcoming field of synthetic biology. Treatment of microbial cells explicitly as a "chemical" species in controlled reaction (growth) environments has allowed fascinating discoveries of elemental formulae of a few species that have guided the modern views on compositions of a living cell. Application of mass and energy balances on living cells has proved to be useful in modeling of bioengine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…[27][28][29][30] Varieties of complexes containing novel synthetic polymers with nitrogen atoms or oxygen atoms and the corresponding complexes with transition metal ions or rare earth metal ions have been synthesized based on complicated chemical reactions. [31][32][33][34] Most of these polymers show interesting magnetic behaviors. However, among so many approaches used for the preparation of organic magnets, the simple method of self-assembly has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Varieties of complexes containing novel synthetic polymers with nitrogen atoms or oxygen atoms and the corresponding complexes with transition metal ions or rare earth metal ions have been synthesized based on complicated chemical reactions. [31][32][33][34] Most of these polymers show interesting magnetic behaviors. However, among so many approaches used for the preparation of organic magnets, the simple method of self-assembly has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…2B). This could probably be explained by the depletion of carbon source in the culture, since carbon is crucial for magnetosome formation as an energy source (Naresh et al 2012). Indeed, carbon is particularly important in the transport process of magnetite synthesis (Schüler and Baeuerlein 1996), and is the limiting source for consumption of nitrogen and iron in the later phase of growth (Naresh et al 2012).…”
Section: Fermentation Performancementioning
confidence: 99%
“…Recently, it was suggested that during MTB growth, iron (Fe) also serves as a nutrient rather than just a storage mineral (Naresh et al, 2012). This was concluded from the fact that Fe was more correlated with C and N, compared to the correlation between C and N which are used mainly as an energy source (C), and for biosynthetic processes (N).…”
Section: Influence Of Environmental Factors On Magnetosome Characterimentioning
confidence: 99%
“…As to the Fe and N relationship, during the lag and exponential growth phases there is a substantial demand of N to form proteins for assembly of magnetosome vesicles, and to transport and incorporate Fe for magnetosome synthesis. After the vesicles assemble, proteins promote the nucleation of Fe crystals leading to MTB magnetosomes (Naresh et al, 2012). This was clearly demonstrated recently by Siponen et al (2013), who showed that the magnetosome associated protein MamP plays the crucial role in magnetite crystal growth inside MTB (Siponen et al, 2013).…”
Section: Influence Of Environmental Factors On Magnetosome Characterimentioning
confidence: 99%